Cardiac implantable electronic device lead-based masses and atrial fibrillation ablation: a case-based illustration of periprocedural anticoagulation management strategies - Lenz, Charles J. (J Interv Card Electrophysiol, 2016)
INTRODUCTION: Cardiac implantable electronic device (CIED) leads frequently develop echogenic masses. However, the nature of these masses is not well understood. In patients in whom atrial fibrillation (AF) catheter ablation is planned, there is concern that transseptal puncture may result in cerebrovascular embolism of these masses. The optimal therapeutic strategy in this setting remains undefined. METHODS: We describe six patients identified over a 6-year period (2008–2014) with device lead-based masses prior to or at the time of AF ablation. We examined the anticoagulation strategy and periprocedural management based on mass identification. RESULTS: In all six patients (age 39–73; four males), the device lead mass was found in the right atrium. The average mass size was 11 ± 1.3 mm. The majority of patients were already on anticoagulation (5/6; 83 %), and an intensified anticoagulation regimen was initiated (INR goal 3.0). In all six patients, the size of the device lead mass decreased on repeat imaging. In two sixths (33 %) patients, the lead-based mass completely resolved within 2 months. The remaining four patients had persistent lead-based masses (average follow-up of 10.9 ± 9.6 months). DISCUSSION: We describe a series of patients with CIED lead-based masses found at the time of ablation. These cases illustrate that lead-based masses can disappear while patients are on high-intensity anticoagulation, most compatible with a thrombotic origin. These early data will need to be assessed in larger cohorts for further validation and evaluation of safety.